PENGARUH KETERLIBATAN KONSUMEN DAN SIKAP TERHADAP KEPERCAYAAN KONSUMEN DALAM PEMANFAATAN WHATSAPP BUSINESS - Lisa Ignacia Norberta; Reza Widhar Pahlevi (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The use of social media in Indonesia is increasing. One of them is the use of the WhatsApp application. In business, WhatsApp is often used as a medium for interacting with customers. Currently, business actors are starting to use the development of the WhatsApp application called WhatsApp Business which is equipped with features that support interaction between sellers and buyers. This interaction is called the consumer engagement process. This research entitled "The Influence of Consumer Engagement and Attitudes on Consumer Trust in the Utilization of WhatsApp Business". The purpose of this study is to determine the effect of consumer engagement and attitudes on consumer trust in using WhatsApp Business. The research was conducted using a quantitative research approach with multiple linear regression methods. This research uses primary data obtained by distributing questionnaires. Samples were taken using a purposive sampling technique from 114 consumer respondents who Samples were taken using the technique purposive sampling to 114 consumer respondents who have purchased goods/services online and have found sellers using WhatsApp by business accounts (WhatsApp Business). The results of this study indicate that consumer engagement and attitudes have a significant influence on consumer trust.